2022
DOI: 10.2196/34951
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility, Acceptability, and Preliminary Efficacy of an App-Based Meditation Intervention to Decrease Firefighter Psychological Distress and Burnout: A One-Group Pilot Study

Abstract: Background Firefighters are often exposed to occupational stressors that can result in psychological distress (ie, anxiety and depression) and burnout. These occupational stressors have only intensified with the onset of the COVID-19 pandemic and will likely persist in the postpandemic world. Objective To address occupational stressors confronting firefighters, we pilot tested a novel, cost-effective, smartphone app–based meditation intervention created… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Digital psychological tools have been proposed as a potential solution [ 37 - 39 ]. In fact, some digital interventions through smartphone apps have proven effective in improving anxiety [ 40 ], depressive symptoms [ 41 ], and work-related burnout [ 42 - 44 ], especially in PC settings [ 45 , 46 ], and also for people with severe mental disorders such as bipolar disorder [ 47 , 48 ].…”
Section: Introductionmentioning
confidence: 99%
“…Digital psychological tools have been proposed as a potential solution [ 37 - 39 ]. In fact, some digital interventions through smartphone apps have proven effective in improving anxiety [ 40 ], depressive symptoms [ 41 ], and work-related burnout [ 42 - 44 ], especially in PC settings [ 45 , 46 ], and also for people with severe mental disorders such as bipolar disorder [ 47 , 48 ].…”
Section: Introductionmentioning
confidence: 99%
“…Healthy Minds Program (HMP) is a mindfulness-based mobile app that may be well suited for use with caregivers of persons with ADRD for several reasons. First, HMP is unique because it teaches mindfulness skills grounded in theory [ 41 ] with empirical support [ 42 - 44 ]. Having a theoretical underpinning is important because it allows the app to be a vehicle for the delivery of evidence-based mindfulness skills.…”
Section: Introductionmentioning
confidence: 99%
“…Having a theoretical underpinning is important because it allows the app to be a vehicle for the delivery of evidence-based mindfulness skills. Second, previous research has shown that HMP reduced emotional distress and burnout in firefighters [ 44 ]; improved psychological distress, stress, social connectedness, and mindfulness in adults [ 43 ]; and reduced stress and increased mindfulness, self-compassion, and human flourishing in medical students [ 42 ]. Third, HMP is free of charge, which increases its reach especially among caregivers who often experience financial burdens because of their role.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it has triggered panic disorders, anxiety, and depression. High prevalence of depression, anxiety, or post-traumatic stress symptoms has been reported among the general population in various countries [ 4 , 5 , 6 , 7 , 8 , 9 , 10 ] In addition, stress and anxiety among various population such as schoolteachers, firefighters, or public workers has also been reported [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%